In silico analyses of leptin and leptin receptor of spotted snakehead Channa punctata. - Amrita Bakshi; Umesh Rai (PLoS ONE, 2022)
The present study, in addition to molecular characterization of leptin (lepa) and its receptor (lepr) of spotted snakehead Channa punctata, is focussed on physicochemical, structural, evolutionary and selection pressure analyses which are poorly elucidated in teleosts in spite of that existence of these genes is well reported in several fish species. The putative full-length Lep and Lepr of C. punctata showed conserved structural and functional domains, especially the residues responsible for structural integrity and signal transduction. Conversely, residues predicted essential for Lep-Lepr interaction displayed divergence between teleosts and tetrapods. Impact of substitutions/deletions predicted using protein variation effect analyser tool highlighted species specificity in ligand-receptor interaction. Physicochemical properties of ligand and receptor predicted for the first time in vertebrates revealed high aliphatic and instability indices for both Lepa and Lepr, indicating thermostability of proteins but their instability under ex vivo conditions. Positive grand average of hydropathy score of Lepa suggests its hydrophobic nature conjecturing existence of leptin binding proteins in C. punctata. In addition to disulphide bonding, a novel posttranslational modification (S-126 phosphorylation) was predicted in Lepa of C. punctata. In Lepr, disulphide bond formation and N-linked glycosylation near WSXWS motif in ECD, and phosphorylation at tyrosine residues in ICD were predicted. Leptin and its receptor sequence of C. punctata cladded with its homolog from C. striata and C. argus of order Anabantiformes. Leptin system of Anabantiformes was phylogenetically closer to that of Pleuronectiformes, Scombriformes and Perciformes. Selection pressure analysis showed higher incidence of negative selection in teleostean leptin genes indicating limited adaptation in their structure and function. However, evidence of pervasive and episodic diversifying selection laid a foundation of co-evolution of Lepa and Lepr in teleosts.